ANATOMICAL STUDIES ON WALLICHIA NANA GRIFF., A WILD PALM OF ASSAM, INDIA - Selim Mehmud; Himu Roy (Reinwardtia, 2020)
MEHMUD, S. & ROY, H. 2020. Anatomical studies on Wallichia nana Griff., a wild palm of Assam, India. Reinwardtia 19(2): 97‒102. ‒‒ The present communicated research is a study based on the observation of free hand transverse section of leaf, stem and root and epidermal morphology of lamina in Wallichia nana, a species distributed in North-eastern states of India. Occurrence of paracytic stomata was noted on both surfaces of the lamina but comparatively more on lower surface. Number of metaxylem vessel recorded in lamina is single whereas, one to two in stem, petiole and roots. Presence of mucilage sacs recorded in the cortex of both petiole and stem.